Tratamento de efluente de fecularia em reator anaeróbio tubular horizontal piloto com meio suporte e agitação - Kuczman, Osvaldo (2012)
The cassava starch industries generate daily a large volume of wastewater effluent that, stabilized in ponds, waste its biogas energy and pollute the atmosphere. To contribute with the reversion of this reality, this manipueira treatment research in one phase anaerobic horizontal pilot reactor with continuous feeding was developed. The reactor was implanted at a starch factory, Toledo, PR, which processes 160 ton cassava day-1 and originates 800 m3 of cassava wastewater. The biomass agitation was obtained by biogas recirculation, pumped by radial compressor, being the support medium set up with 15 x 4 cm bamboo pieces. The cassava wastewater, in natura, flowed by a sand and clay separating chamber, feeding the reactor with volume measured by an hydrometer. The experimental design was a completely randomized design, with the responses submitted to multivariate analysis and to statistical quality control through R 13.0 and Minitab 15.1.0.0 softwares, respectively. The average organic loadings in chemical oxygen demand (COD) were 0.556; 0.670; 0.678; 0.770 and 0.902 g L-1; and in volatile solids (VS) 0.659; 0.608; 0.570; 0.761 and 0.816 g L-1 at the hydraulic retention times (HRT) of 13.0; 11.5; 10.0; 7.0 and 7.0 days. The average reductions for COD, at the same order that the HRTs, were 88; 80; 88; 67 and 70% and for VS 76; 77; 65; 61 and 53%. The biogas productions relatively to COD consumed were 0.368; 0.795; 0.891; 0.907 and 0.626 Lg-1, relatively to VS consumed were 0.524; 0.930; 1.757; 0.952 and 0.981 Lg-1 and volumetrically 0.131; 0.330; 0.430; 0.374 and 0.377 L L-1 d-1, with an average methane content of 56%. The 10.0 days HRT was evaluated with an average temperature of 27.7 °C and the others with temperatures ranging from 21.2 to 23.5 °C. The agitation efficiency was proven as it increased the reactor s performance, in spite of a 2.3 °C average reduction at the temperature. The stability indicators pH and volatile acidity/total alkalinity (VA/TA) relation remained between 6.51 to 7.45 and 0.11 to 0.82, respectively. Although the relation VA/TA has presented risk values, the reactor remained stable, possibly due to the support medium presence